The Effect of Adding Magnesium Sulfate to Lidocaine Compared with Paracetamol in Prevention of Acute Pain in Hand Surgery Patients Under Intravenous Regional Anesthesia (IVRA) - Mirkheshti, Alireza (Medknow Publications & Media Pvt Ltd, 2012)
INTRODUCTION: This study was done to compare the analgesic effects of “magnesium plus lidocaine”, “paracetamol plus lidocaine”, and “placebo plus lidocaine” on block characteristics for intravenous regional anesthesia (IVRA) in patients undergoing upper extremity orthopedic surgery. METHODS: In a double-blind, placebo-controlled randomized clinical trial, 90 patients were selected and entered randomly into three study groups after applying the inclusion and exclusion criteria. Time to start of the sensory and motor block were measured separately and also the duration of these two block types were measured. Post-op pain assessment was measured using a numeric rating scale. Venous samples were checked and compared regarding blood gas and pH measurements. RESULTS: The time from drug injection to sensory block onset was the shortest in the magnesium plus lidocaine group; the time from drug injection to the time of motor block onset was the shortest in the lidocaine plus magnesium group; the duration of the motor block was the longest in the lidocaine plus magnesium group. DISCUSSION: Addition of magnesium lidocaine in patients undergoing upper extremity orthopedic operations using IVRA decreases significantly the time gap between drug administration and the start of the block; also, this drug combination increases the IVRA block length, while paracetamol does not have such a significant effect.